Baghdad and Jerusalem: musicians and dancers in the painted ceilings of the Cappella Palatina in Palermo - Johns, J (2015)
The subject of this paper is iconography and iconology in the painted ceilings covering the space that was at one and the same time the royal hall and the nave of the chapel in the principal palace in Palermo of the Norman kings of Sicily